Fenomena Perilaku Belanja Online sebagai Pilihan Konsumsi pada Laki-laki Usia Produktif - Riska Puspita (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Technological advances have a major impact on all human activities. One of them is shopping activities. Someone only by using the internet that is in a cell phone can carry out various shopping transactions easily. The ease of transactions in online shopping is also another supporting factor for choosing online shopping compared to traditional shopping. This causes changes in consumer spending behavior, including male consumers. Another phenomenon that supports online shopping activities is activities that are limited due to the development of the COVID-19 virus which continues to increase until now. This study uses a type of qualitative research using a phenomenological approach. The research involved one man of productive age who had online shopping experience in meeting his needs during a pandemic. Data collection was carried out using interview techniques. The results of the study explain that men of productive age choose online shopping because of intrinsic and extrinsic motivation. Intrinsic motivation consists of perceptions of convenience and practicality in online shopping, trust, hobbies they have, the desire to try new things and a sense of security in terms of health when shopping. Extrinsic motivation that causes online shopping behavior in men of productive age consists of the social environment, organizational/workplace culture, promotions/discounts, more economical prices, trends, availability and variety of products and attractive advertisements.